The Impact of Utilising a Wobble Board for Training on The Precision Archery Shots a 30-Meter Distance among Athletes - Ladia Apsari Hasibuan; Herli Pardilla; Muhammad Iqbal (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. This study aims to find out the effect of the training using the wobble board method on the body balance and the accuracy of archery at a distance of 30 metres of archery athletes. Materials and methods. The research used a quasi-experimental research type with the One Group Pretest-Posttest Design. The samples in this study were 12 athletes taken from the archery athletes of Selabora Panahan aged 13-17 years old. The instruments used were the Stork Test and a 30 metre archery. The data analysis technique used the Normality Test assisted by SPSS 16 software and the Homogeneity Test to determine whether the variance of samples taken from the same population was equal or not. Results. Based on the research findings, it can be obtained: analysis of body balance of archery athletes of Selabora Panahan, obtained t value (6.199) > t table (2.20), and p value (0.000) < 0.05, based on data analysis for the accuracy of archery athletes of Selabora Panahan obtained the value of t count (5.437) > t table (2.20), and the value of p (0.000) < 0.05. Conclusions. it can be concluded that there is an effect of training using a wobble board on the body balance and accuracy of archery at a distance of 30 meters of the archery athletes.